The sustainability of communication for behavioural impact (COMBI) programme in the prevention and control of dengue in Kelantan - Abdullah Husam, A Shukor (2014)
COMB I programme is one of the approaches used by the Ministry of Health Malaysia (MOH) on dengue prevention and control. This programme applies the concept of social mobilisation process that prompts individuals and their families to take appropriate action against dengue. Even though the programme has been started ten years ago in Kelantan, the sustainability of the programme has yet to be assessed The study aimed to evaluate the status and explain factors influencing the sustainability of COMB I programme in Kelantan The study adopted a mixed-method, non-randomised, comparative crosssectional community study. Kampung Nelayan Kandis (KNK) and Kampung Satang Merbau (KBM) were selected as intervention areas with Kampung Nipah (KN) and Kampung Rawa (KR) as their respective controls. The quantitative method in the study was based on secondary data and knowledge, attitude and practice (KAP) survey. The qualitative method applied in the study included the use of in-depth interview and document review. The first part of the study combined quantitative and qualitative methods to evaluate the performance of the COMBI programme over time, that is, whether or not the programme was sustainable at least three or five years after the cessation of formal programme activities. Fourteen indicators grouped into three main categories that is maintenance of health benefits achieved through the initial programme, continuation of programme activities and capacity building in a community, were used to evaluate the sustainability of the programme. The evaluation on each indicator for both KNK and KBM were scored using the 'Five-Point Scale'. Subsequently, a 'Five-Interval Sustainability Score' was used to determine the level of sustainability in KNK and KBM. The second part of the study explains the factors influencing the sustainability of the programme from qualitative perspective In KNK, the incidence rate of dengue over five and half years after formal programme period was significantly higher than over five and half years before official programme period (p = 0.040). In contrast, the incidence rate of dengue in KBM over four years after official programme period was significantly lower than over four years before the formal programme period (p = 0.026). On the contrary, the means of Aedes index (AI), Breteau index (BI) and Container index (CI) over five and half years after the cessation of formal programme activities in KNK were higher in KNK compared to KN. The differences between the means indices were statistically significant in AI (p = 0.036), BI (p = 0.035) and CI (p = 0.021 ). In KBM, the means of AI, BI and CI over four years after official COMBI programme period were higher than over four years before formal programme period. The differences between the means indices were statistically significant in AI (p = 0.002), BI (p = 0.002) and Cl (p = 0.009). On the other hand, the mean scores for total KAP, knowledge, attitude and practice were higher in KNK compared to KN. However, the differences between the mean scores were only significant in total KAP (p = 0.043) and practice (p = 0.003). The mean scores for KBM were higher than the mean scores for KR in total KAP, knowledge, attitude and practice. However, the differences between the mean scores were only significant in total KAP (p = 0.022) and practice (p = 0.017). This study also discovered that some indicators of the continuity of programme activities showed substantial deterioration compared to during formal programme period in both intervention areas. On the other hand, other indicators showed that the community in the intervention areas continued to organise activities related to the prevention and control of dengue. It was also disclosed that the capacity of KNK community to organise and mobilise themselves towards dengue prevention and control were as good as during formal programme period or better than its control area. In contrast, those capacities in KBM were similar to the control area or showed substantial deterioration compared to during official programme per~od. Based on the 'Five-Point Scale' and 'FiveInterval Sustainability Score', the sustainability scores of KNK and KBM were 3.5 and 2.57, respectively. Accordingly, COMBI programmes in KNK and KBM were rated as "well sustained" and "not sustained", respectively. The sustainability of COMBI programme in KNK was influenced by the solid socio-cultural foundation for dengue control, the capacity of implementing organisation, credibility and quality of leadership as well as active contribution from women as a major support group for COMB! work. The COMB I programme in KBM was not sustained largely due to over-dependence on supervision by the MOH and weak socio-cultural foundation for dengue control It seems that it is not so much the design, structure, content or organisation of COMBI programme that matter to its sustainability as compared to the dynamics or functioning of the community that adopts and internalise the principles and objectives of sustainability. Empowered communities such as KNK seemed to be able to sustain thus benefiting from it whereas dysfunctioning communities as shown by KBM ended up making an extra burden of it.